A power-law liquid food flowing through an uneven channel with non-uniform suction/injection. (December 2019) - Li, Botong; Yang, Yikai; Chen, Xuehui
Highlights: Accumulation of impurities in liquids leads to non-uniform deposit distributions. Non-uniform deposit distributions cause uneven walls with varying permeability. Three kinds of boundary shapes and suction/injection conditions are studied. The condiment oyster sauce satisfying the power-law model is assessed. Abstract: In filtration/permeation, precipitation and accumulation of impurities in fluids will lead to uneven walls in a filter duct, which in turn causes non-uniform suction/injection. In the present article, we numerically investigate the fluid flow and heat transfer of a power-law fluid food in the heating process through an uneven channel with non-uniform suction/injection. Three different sets of channel surfaces and boundary suction/injection conditions are considered: the channel surface and the permeability are depicted as linear functions, quadratic functions, and trigonometric functions, respectively. This study investigates a traditional Chinese condiment, oyster sauce, a typical type of power-law fluid. The velocity, temperature, and pressure fields are investigated under the impacts of various parameters, such as the power-law index n and the suction/injection parameter v w . The findings reveal that the velocity and temperature curves have peaks and troughs, which differ from those obtained with a uniform suction/injection and even boundary surface.